The Importance of Teacher Competences in Early School Education - Zubel, Magdalena; Mielnikiewicz, Joanna; Pater, Patrycja (Journal of Education, Technology and Computer Science, 2021)
The competences of an early school education teacher play an important role in the process of teaching and upbringing a child at this stage of education. In order to properly develop children’s skills, special attention should be paid to the role played by a competent teacher who guides pupils’ development, gives them knowledge about the world and prepares them for further learning. The aim of the article is to explain the importance of teacher competences in the work with children in early school education. The article has been written on the basis of a bachelor’s thesis, and the presented research results have been based on the responses obtained from the questionnaires addressed to early school education teachers and children’s parents. The research has shown that teacher competences at this stage of education play an important role in the teaching process. According to the respondents, the required competences include psychological, pedagogical, didactic, methodological, and substantive competences. Taking up this issue resulted from the experience gained during the internships, when it was observed that a competent teacher has greater opportunities to carry out educational tasks.